Novelties to Compositae Family in Rio Grande do Sul State Flora - Deble, Leonardo Paz; Oliveira-Deble, Anabela Silveira de (Balduinia, 2014)
Twelve new records to Compositae from Rio Grande do Sul Flora are proposed: Soliva macrosperma Cabrera (Tribe Anthemidae); Baccharis coronata Giuliano, Baccharis flabellata Hook. & Arn., Conyza pampeana (Parodi) Cabrera, Conyza serrana Cabrera, and Podocoma spegazzini Cabrera (Tribe Astereae); Micropsis ostenii Beauveard, Micropsis spathulata (Pers.) Cabrera, and Pseudognaphalium luteo-album (L.) Hilliard & B.L. Burtt (Tribe Gnaphalieae); Trichocline humilis Less. (Tribe Mutisieae); Stenachaenium adenanthum (Sch.-Bip. ex Krasch.) Krasch. (Tribe Plucheae); and Chrysolaena propinqua (Hieron.) H. Rob. var. canescens (Chodat) Dematt. (Tribe Vernonieae). The identity of Hysterionica nidorelloides DC. is defined, being Hysterionica montevidensis Baker its synonym. A superfluous combination under Viguiera santacatarinensis is included as new synonym. Isostigma riedelii (Baker) Chodat is excluded to Rio Grande do Sul Flora, and two new combinations are proposed: Calea paraguayensis (Kuntze) Deble and Vernonanthura nudiflora f. albiflora (Matzenb.) Deble.